Measuring sunk costs in agricultural and food industry assets: why some assets sell below appraisal - Boland, Michael A.; Crespi, John M.; Turner, Tracy M. (My University, 2015)
Asset obsolescence or external obsolescence is a decline in the economic value of capital because of a decrease in demand for the capital’s services. Measurements of sunk costs typically use appraised values of capital. In food and agricultural industries facing asset obsolescence due to government policy, appraised values may be greatly overstated and this has implications for research on industrial structure. A theoretical model to account for the appraisal error is developed and the method is applied to the U.S. sugar beet industry. The sugar beet industry displays symptoms of asset obsolescence. Our estimates indicate that plant appraisals using currently accepted practices greatly overstated the true value of these assets in 2006.
Keywords: Sunk costs; Obsolescence; Real estate appraisal; Stranded capital; Sugar beet